Position of Cyanobacteria and Algae in Origin of Life - Prasad, Vishwanath (Academic Voices: A Multidisciplinary Journal, 2011)
Our beautiful planet, the earth was originated 4.5 billion years ago in our solar system. Between 3.5 – 4.0 billion years ago, after several events of chemical evolution and modification in the earth's atmosphere, the first life, amino acid and nucleic acid, called ecobiont or protobiont, was originated in abiogenesis phase and started protobiology phase. The life has evolved into three domains: age of Eobacteria, Cyanobacteria and Eukaryotes which ultimately evolve into land plants. The purpose of this article is to add some recent information about origin of life and position of cyanobacteria in the evolution of higher plants. Keywords Origin, life, Ecobiont, Cyanobacteria, algae. DOI: http://dx.doi.org/10.3126/av.v1i0.5316 Academic Voices 2011; 1: 94-99